A sacrificial protective layer as fouling control strategy for nanofiltration in water treatment. (1st July 2022) - Li, Sihang; Meng, Huanna; Wang, Haihua; Vrouwenvelder, Johannes S.; Li, Zhenyu
Highlights: A coating-decoating-recoating strategy for membrane antifouling was developed. CMCS was used as sacrificial protective layer of membrane against NOM fouling. Decoating removed protective layer with foulants to restore membrane performance. The protective layer can be regenerated by recoating in situ . Sacrificial protective layer showed sustainable performance during long term test. Abstract: High-performance nanofiltration (NF) membrane with super antifouling capability as well as reusability is highly desired in water treatment. A new antifouling strategy by a coating-decoating-recoating cycle was investigated for effective removal of fouling and restoring the original membrane performance. The functional membrane surface was fabricated by in-situ coating a 'green' and biodegradable carboxymethyl chitosan (CMCS) layer as physical barrier. The CMCS layer can be decoated and re-coated by simple procedures. Results showed that (i) the CMCS layer enhanced surface hydrophilicity, surface smoothness and fouling resistance of NF membrane, (ii) both the unfouled and fouled CMCS layer were easily decoated by the strong acid solution, (iii) the CMCS layer was easily re-coated by facile recoating and (iv) the water flux recovery ratio of membrane with coating layer was maintained more than 88.8% during fouling testing by natural organic matter (NOM) after four sequential cycles of coating, decoating and recoating process. The re-coated membrane exhibited stable, improved membrane operational and antifouling performance. The coating-decoating-recoating approach is proven to be low-cost and eco-friendly strategy for NOM fouling control on NF membrane in water treatment applications. Graphical abstract: Image, graphical abstract